The Supreme Court and the American elite, 1789-2020 - Powe, L. A. Scot (Constitutional thinking., 2021)
"In this engaging-and disturbing-book, a leading historian of the Court reveals the close fit between its decisions and the nation's politics, beginning with the creation of the Constitution and ending with the confirmation hearing of Brett Kavanaugh. Rendering crisp (and often controversial) judgments on key decisions from Marbury v. Madison to the War on Terror, Lucas Powe shows how virtually every major Supreme Court ruling, however deftly framed in constitutional terms, suited the wishes of the most powerful politicians of the time. This history reflects a changing Court, from the country's early struggles over commerce and transportation to the torturous justifications of slavery before the Civil War, to a post-New Deal interest in ending segregation, controlling criminal procedure, and addressing knotty questions arising from the Cold War. Through all of this the Court emerges as part of a ruling regime, doing its best to implement the regime's policies. Drawing on more than four decades of thinking about the Supreme Court and its role in the American political system, this book offers a new, clear, and troubling perspective on American jurisprudence, politics, and history. This new edition adds two chapters detailing the history of the Court since 2008. The first looks at the centrist jurisprudence of Justice Anthony Kennedy and his dominant presence as the decisive vote in a series of 5-4 decisions. The second looks at the aftermath of Justice Antonin Scalia's death and the Republican control of the Court"--